Effects of vibratory feedback stimuli through an oral appliance on sleep bruxism: A 14-week intervention trial - Kohei Maejima; Masayuki Takaba; Yuka Abe; Hironobu Ohara; Risa Aoki; Megumi Matsuyama; Shiori Okuhara; Kazuyoshi Baba (Elsevier, 2024)
Background/purpose: Various biofeedback stimulation techniques for managing sleep bruxism (SB) have recently emerged; however, the effect of the successive application of vibratory feedback stimulation has not been clarified. This study aimed to elucidate the effect of vibration feedback stimulation via an oral appliance (OA) on SB. Materials and methods: This prospective, single-arm, open-label intervention study included 20 participants diagnosed with "definite" SB who wore a specially designed OA for 98 nights at home. A force-based SB detection system triggered a vibrator attached to the OA. Vibratory stimulation was withheld during the first 3-week adaptation period (weeks 1-3), applied during the 9-week stimulation period (weeks 4-12), and withheld again during the post-stimulation period (weeks 13-14). The number and duration of SB events per hour of sleep were calculated based on piezoelectric signals recorded with the OA-based vibration feedback device and compared between weeks 3 and 4, 8, 12, and 14 and between weeks 12 and 14 using the Friedman test (post-hoc test with Bonferroni correction). Results: The duration of SB events significantly decreased after vibratory stimulation (weeks 3 versus 4, 8, and 12: P < 0.001, P = 0.026, and P = 0.033, respectively) and then significantly increased upon cessation of vibratory stimulation after the stimulation period (weeks 12 versus 14: P < 0.001). Conclusion: Contingent vibratory stimulation through an OA-based vibration feedback device may suppress SB-related masticatory muscle activity continuously for 9 weeks and may be an effective alternative for managing SB.